Analisis Dan Perancangan Sistem Absensi Berbasis RFID Pada Majelis Tafsir Al-Qur’an (MTA) Perwakilan Kota Jambi - Sambodo, Prakoso Setyo; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
The Majlis Tafsir Al-Qur’an Foundation (MTA) has several activities such as social service, blood donation, health education and routine recitation which are held in all branches and representatives. With the large number of inmates and general people participating in the recitation activities, participants and those not present at the recitation activities should be recorded and recapitulated in order to find out the number and activeness of the residents who come to the study. The data collection process will take a long time because they have to be called one by one and ask the reason for the absence of residents. To overcome this time-consuming problem, the researcher conducted a system analysis that was carried out with the aim of designing a system of attendance prototype systems based on Radio Frequency Identification (RFID) to facilitate the data collection process and attendance reporting. In building this attendance system using website-based programming using the PHP programming language and MySQL database processing, but this research is only limited to the analysis and role of the system using prototype modeling. This study produced a solution to the problem, namely the design of RFID-based attendance systems, where all attendance and recap attendance processes are carried out in RFID-based attendance systems so that the output is automatically present attendance report after the assisted residents finish attaching RFID tags. constraints on the attendance process for a long time.